Correlation of Work Motivation toward the of Human Resource Performances at Al Islam Polytechnique of Bandung in 2017: Correlation of Work Motivation toward the of Human Resource Performances at Al Islam Polytechnique of Bandung in 2017 - Dian Nuramdiani; Nieke Resmiati; Yoppie Kaerunnisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Al Islam Bandung, 2018)
As one of higher education institutions, Politeknik Al Islam Bandung should be able togive optimal services in producing qualified graduates. As one living organisms thathas a major role in achieving goals of higher education institutions, the Politeknik AlIslam Bandung requires qualified and profesional human resources. The aim of thisstudy is to find out the information about human resources in Politeknik Al IslamBandung, and also to know the correlation between work motivation owned by itshuman resources and resulted performance. The study was conducted on 37respondents consisting of lecturers and staffs of Politeknik Al Islam Bandung. Theresults show that about 83.8% of human resources of Politeknik Al Islam Bandunghave high motivation, with an average of 120,4. The correlation between workmotivation and performance conducted by them belongs to strong category, which is proved by r coefficient value of 0,695. The significance test was carried out with asignificance level of 5% to prove positive and significant relationships between thework motivation and performance of the human resources. The results show that tcountis greater than ttable (5.72 > 1.689). It means that this study has succesfully proved thatthere is a strong relationship between work motivation and performance.